THE SIGNIFICANCE OF TEXT AND DISCOURSE IN ENHANCING COMMUNICATIVE COMPETENCE (Scientific journal of the Fergana State University, 2024)
The given article deals with the significance of text and discourse in developing communicative competence of students who are learning English as a second or as a foreign language. Text and discourse are indispensable aspects of linguistic forms. Various researches on text and discourse have been made by linguistic exponents. Discourse analysis can be applied to any text, that is, to any problem or situation. Every text is conditioned, and inscribes itself within a given discourse. Discourse analysis will, thus, not provide absolute answers to a specific problem, but enables us to understand the conditions behind a specific "problem" and makes us realize that the essence of that "problem", and its resolutionText and discourse are interrelated in terms of enhancing studentsʼ communicative competence.